The Future of Gas in Decarbonising European Energy Markets – the need for a new approach - Stern, J (Oxford Institute for Energy Studies, 2017)
The European gas industry has argued that gas can be a bridging fuel in the transition to decarbonised energy markets because of the advantages of switching from coal to gas, and the role of gas in backing up intermittent renewable power generation. While this remains a logical approach for some countries, in others it has proved either not relevant, or generally unsuccessful in gaining acceptance with either policymakers or the environmental community. Policy decisions will be taken in the next 5-10 years which will irreversibly impact the future of gas in the period 2030-50. A paradigm shift in commercial time horizons and gas value chain cooperation will be necessary for the industry to embrace decarbonisation technologies (such as carbon capture and storage), which will eventually be necessary if gas is to prolong its future in European energy markets. To ensure a post-2030 future in European energy balances, the gas community will be obliged to adopt a new message: `Gas can Decarbonise’ (and remain competitive with other low/zero carbon energy supplies). It will need to back up this message with a strategy which will lead to the decarbonisation of methane starting no later than 2030. Failure to do so will be to accept a future of decline, albeit on a scale of decades, and to risk that by the time the community engages with decarbonisation, non-methane policy options will have been adopted which will make that decline irreversible.